Efficacy of a minimally guided internet treatment for alcohol misuse and emotional problems in young adults: Results of a randomized controlled trial. (December 2021) - Frohlich, Jona R.; Rapinda, Karli K.; Schaub, Michael P.; Wenger, Andreas; Baumgartner, Christian; Johnson, Edward A.; O'Connor, Roisin M.; Vincent, Norah; Blankers, Matthijs; Ebert, David D.; Hadjistavropoulos, Heather D.; Mackenzie, Corey S.; et al.
Highlights: Cognitive-behavioural therapy (CBT) and motivational interviewing (MI) can be readily adapted for brief, minimally guided, online interventions. Minimally guided online treatment is beneficial for hazardous drinking, mood difficulties, and quality of life in the short-term among young adults. Strategies designed to increase treatment engagement will likely mitigate the risk of attrition in future programs. Future versions of the Take Care of Me program are still needed to determine long-term effects and differential responses to treatment. Abstract: Objective: Many young adults struggle with comorbid alcohol misuse and emotional problems (i.e., depression and anxiety). However, there is currently a paucity of evidence-based, integrated, accessible treatment options for individuals with these comorbidities. The main goal of this study was to examine efficacy of a novel online, minimally guided, integrated program for comorbid alcohol misuse and emotional problems in young adults. Method: The study was an open-label two-arm RCT. Participants ( N =  222, M age  = 24.6, 67.6% female) were randomized to one of two conditions: the Take Care of Me program (an 8-week, online integrated treatment condition consisting of 12 modules), or an online psychoeducational control condition. Intervention modules incorporated content based on principles of cognitive behavioral therapy and motivational interviewing. Participants completed assessment data at baseline, at the end of treatment (i.e., 8 weeks), and at follow-up (i.e., 24 weeks). Data were analyzed using generalized linear mixed models. Results: We observed that participants in the treatment condition showed larger reductions in depression, hazardous drinking, as well as increases in psychological quality of life and confidence at the end of treatment. We did not find group differences on total alcohol use at follow-up, but participants in the treatment group reduced their hazardous drinking and improved their quality of life at 24-week follow-up. Conclusions: Our study provides promising initial evidence for the first iteration of the comorbid alcohol misuse and emotional problems online program.